A motorized solid-state phantom for patient-specific dose verification in ion beam radiotherapy. (3rd September 2015) - Henkner, K; Winter, M; Echner, G; Ackermann, B; Brons, S; Horn, J; Jäkel, O; Karger, C P
Abstract: For regular quality assurance and patient-specific dosimetric verification under non-horizontal gantry angles in ion beam radiotherapy, we developed and commissioned a motorized solid state phantom. The phantom is set up under the selected gantry angle and moves an array of 24 ionization chambers to the measurement position by means of three eccentrically-mounted cylinders. Hence, the phantom allows 3D dosimetry at oblique gantry angles. To achieve the high standards in dosimetry, the mechanical and dosimetric accuracy of the phantom was investigated and corrections for residual uncertainties were derived. Furthermore, the exact geometry as well as a coordinate transformation from cylindrical into Cartesian coordinates was determined. The developed phantom proved to be suitable for quality assurance and 3D-dose verifications for proton- and carbon ion treatment plans at oblique gantry angles. Comparing dose measurements with the new phantom under oblique gantry angles with those in a water phantom and horizontal beams, the dose deviations averaged over the 24 ionization chambers were within 1.5%. Integrating the phantom into the HIT treatment plan verification environment, allows the use of established workflow for verification measurements. Application of the phantom increases the safety of patient plan application at gantry beam lines.